Genetic mapping of AhVt1, a novel genetic locus that confers the variegated testa color in cultivated peanut (Arachis hypogaea L.) and its utilization for marker-assisted selection - Chen, Hao; Yang, Xinlei; Xu, Rirong; Chen, Xiangyu; Zhong, Haifeng; Liu, Nian; Huang, Li; Luo, Huaiyong; Huai, Dongxin; Liu, Wenjing; Chen, Yuhua; Chen, Jianhong; et al. (Frontiers in Plant Science, 2023)
Peanut (Arachis hypogaea L.) is an important cash crop worldwide. Compared with the ordinary peanut with pure pink testa, peanut with variegated testa color have attractive appearance, and a higher market value. In addition, the variegated testa represents a distinct regulation pattern of anthocyanin accumulation in integument cells. In order to identify the genetic locus underlying variegated testa color in peanut, two populations were constructed from the crosses between Fuhua8 (pure-pink testa) and Wucai (red on white variegated testa), Quanhonghua1 (pure-red testa) and Wucai, respectively. All the seeds harvested from the F1 individuals of both two populations showed the variegated testa type with white trace. Genetic analysis revealed that the pigmentation of colored region in red on white variegated testa was controlled by a previous reported gene AhRt1, while the formation of white region (un-pigmented region) in variegated testa was controlled by another single genetic locus. This locus, named as AhVt1 (Arachis hypogaea Variegated Testa 1), was preliminary mapped on chromosome 08 through bulked sergeant analysis sequencing. Using a secondary mapping population derived from the cross between Fuhua 8 and Wucai, AhVt1 was further mapped to a 1.89-Mb genomic interval by linkage analysis, and several potential genes associated with the uneven distribution of anthocyanin, such as MADS-box, MYB and Chalcone synthase-like protein, were harbored in the region. Moreover, the molecular markers closely linked to the AhVt1 were developed, and the new variegated testa peanut lines were obtained with the help of marker-assisted selection. Our findings will accelerate the breeding program for developing new peanut varieties with “colorful” testa colors and laid a foundation for map-based cloning of gene responsible for variegated testa.